Study of growth and broadband FMR spectroscopy in PLD grown Y3Fe5O12/Gd3Ga5O12 thin films. (27th October 2022) - Satapathy, S; Pant, R P; Maurya, K K
Abstract: We report the structural and magnetization dynamics of pulsed laser ablated Y3 Fe5 O12 (YIG) thin films grown on gadolinium gallium garnet (GGG[110]) substrate. The co-planar waveguide ferromagnetic resonance measurement was performed to study the thickness and inhomogeneity effect on damping constant. We also estimated the effective demagnetization ( 4 π M eff ) value which was lower than that of single-crystalline bulk YIG. A detailed line width analysis revealed the significant two-magnon scattering and inhomogeneity contribution to damping which varied for different thickness films. The Gilbert damping constant ( α ) of the grown film was found to be lowest in the case of 100 nm film (≈3 × 10 −4 ), and the corresponding inhomogeneous broadening (Δ H O ) was recorded to be 77 Oe. Further angular measurements on 100 nm thin film revealed the presence of strong uniaxial magnetic anisotropy field of 735 Oe at 10 GHz RF frequency.